Classificação de biodiesel na região do visível - Germano Véras; Anna Luiza Bizerra de Brito; Adenilton Camilo da Silva; Priscila da Silva; Gean Bezerra da Costa; Lorena Cristina Nóbrega Félix; David Douglas de Sousa Fernandes; Marcelo Marques de Fontes (Química Nova, 2012)
Classification of biodiesel by oilseed type using pattern recognition techniques is described. The spectra of the samples were performed in the Visible region, requiring noise removal by use of a first derivative by the Savitzky-Golay method, employing a second-order polynomial and a window of 21 points. The characterization of biodiesel was performed using HCA, PCA and SIMCA. For HCA and PCA methods, one can observe the separation of each group of biodiesel in a spectral region of 405-500 nm. SIMCA model was used in a test group composed of 28 spectral measurements and no errors are obtained.